2022
DOI: 10.3390/bioengineering9110616
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Key Biomechanical Parameters According to the Expertise Level in Runners at Different Running Speeds

Abstract: Running has become increasingly popular worldwide. Among runners, there exists a wide range of expertise levels. Investigating the differences between runners at two extreme levels, that is novices and experts, is crucial to understand the changes that occur as a result of multiple years of training. Vertical oscillation of center of mass (CoM), stride frequency normalized to the leg length, and duty factor, which describes the step time relative to the flight time, are key biomechanical parameters that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In support of this, it has recently been demonstrated that individuals adopt a technique that avoids overburdening individual muscles (i.e., minimization of individual muscle fatigue) during walking, despite this leading to a higher overall metabolic cost [ 165 ]. This may therefore explain some conflicting findings between our review and studies that compared running biomechanics between groups of runners differing in running performance or training experience [ 166 169 ].…”
Section: Discussionmentioning
confidence: 86%
“…In support of this, it has recently been demonstrated that individuals adopt a technique that avoids overburdening individual muscles (i.e., minimization of individual muscle fatigue) during walking, despite this leading to a higher overall metabolic cost [ 165 ]. This may therefore explain some conflicting findings between our review and studies that compared running biomechanics between groups of runners differing in running performance or training experience [ 166 169 ].…”
Section: Discussionmentioning
confidence: 86%
“…Even in subgroups of individuals with similar sprint velocities, a range of SF and step length combinations are present ( Hunter et al, 2004 ). In addition, SF was shown to be more variable in novice than expert runners, independently of the running speed (10 and 15 km/h) ( Fadillioglu et al, 2022 ). Furthermore, Bonnaerens et al (2021) demonstrated that external forces were lower in recreational runners that run with higher DF and SF values (although non-significant for SF).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 8 ] investigated the effects of different shoe-heel heights on pregnant women’s walking balance, providing new insights on reducing fall risks in this population. Fadillioglu et al [ 9 ] compared running patterns in novice runners vs. expert runners, and identified the key spatiotemporal and kinematic parameters indicating better running performance. In addition, Fernandes et al [ 10 ] conducted a comprehensive review on whether swimming performance is related to kinematic parameters, i.e., intracycle velocity variations.…”
Section: Evaluation Of Motion Patterns Using Validated Biomechanical ...mentioning
confidence: 99%